Inuit Throat-Games and Siberian Throat Singing: A Comparative, Historical, and Semiological Approach - Nattiez, Jean-Jacques (Ethnomusicology, 1999)

De l’oreille au cœur. Naissance du chant religieux en langues amérindiennes dans les missions de Nouvelle-France, 1600-1650 - Dubois, Paul-André (Septentrion, 1997)

Naissance du cantique en langue vernaculaire dans les missions de Nouvelle-France et conquête des langues amérindiennes : une relation - Dubois, Paul-André (Recherches amérindiennes au Québec, 1997)

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Naissance et évolution de la musique religieuse en langue vernaculaire dans les missions amérindiennes de Nouvelle-France au cours de la première moitié du XVIIième siècle - Dubois, Paul-André (Université Laval, 1996)

Visions of Sound: Musical Instruments of First Nation Communities in Northeastern America - Diamond, Beverley; Cronk, M. Sam; Rosen, Franziska von (University of Chicago Press, 1995)

Quebec Sings "E Uassiuian": The Coming of Age of a Local Industry - Grenier, Line; Morrison, Val (Popular Music: Style and Identity, 1995)

"Echoes of a Proud Nation": Reading Kahnawake's Powwow as a Post-Oka Text - Blundell, Valda (Canadian Journal of Communication, 1993)
Abstract: After presenting one history of North American powwows as sites where aesthetic forms are deployed to transform meanings about aboriginal peoples, an analysis is offered of the powwow produced by the Kahnawake Mohawk a year after their involvement in the Oka crisis. Résumé: Cet article présente d'abord une histoire des powwows nord-américains comme lieux de déploiement de formes esthétiques qui modifient le sens et la signification des peuples autochtones. L'article analyse ensuite le powwow des Mohawks de Kahnawake qui a eu lieu un an après la crise d'Oka.
Keywords: Cultural producers

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

“La Mariouche est pour un blanc” (Jack Monoloy). À propos de la question des minorités dans la chanson canadienne-française - Mathis, Ursula (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 1992)

Voces Cantantes in Vestro: History of Research on Music among the Wabanaki - Morrison, Ann (Papers of the Algonquian Conference / Les Actes du Congrès des Algonquinistes, 1991)

"Not knowing" and the study of Native music cultures: Introductory comments - Diamond Cavanagh, Beverley (Ethnomusicology in Canada, 1990)